KEPEMIMPINAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN DI ERA COVID-19 - Nashran Azizan; Dian Armanto; Maulana Arafat Arafat (DIRASATUL IBTIDAIYAH, 2022)
Abstract Quality education comes from the quality of the teachers. Especially the competence of teachers from the professional, pedagogical, moral, and social aspects. Competent teachers are seen from their performance results, while to realize quality performance, motivation is needed from the principal. This study aimed to look at the leadership attitude of school principals in improving the quality of education during the COVID-19 pandemic. This research uses quantitative methods. The sample was teachers at SDN 200212/2 Padangsidimpuan schools, and the sample was determined using a random sampling technique. They are collecting data using a questionnaire with a Likert measurement scale. Data analysis used descriptive statistics using the 2022 version of STATCAL software. The study results describe that the leadership attitude carried out by the principal of SDN 200212/2 Padangsidimpuan city, North Sumatra province is excellent at 93% based on responses from 20 teachers. Meanwhile, teachers who are in a neutral position see only 5% of the principal's leadership, and 2% of teachers think that the principal rarely rewards work performance. It is never fair to give sanctions to subordinates who fail to carry out their duties. Keywords: Principal, quality of education, COVID-19 pandemic Abstrak Pendidikan yang bermutu berasal dari kualitas gurunya. Terutama kompetensi guru dari aspek profesional, pedagogi, moral kerja, dan sosialnya. Guru yang berkompetensi dilihat dari hasil kinerjanya, sedangkan untuk mewujudkan kinerja yang bermutu perlu motivasi dari kepala sekolah. Tujuan penelitian ini untuk melihat sikap kepemimpinan kepala sekolah dalam meningkatkan mutu pendidikan di masa pandemi COVID-19. Penelitian ini memakai metode kuantitatif. Sampelnya adalah guru-guru di sekolah SDN 200212/2 Padangsidimpuan, sampel ditentukan dengan menggunakan teknik random sampling. Pengumpulan data menggunakan kuesioner dengan skala pengukuran likert. Analisis data menggunakan statistik deskriptif menggunakan software STATCAL versi 2022. Hasil penelitian menguraikan bahwa sikap kepemimpinan yang dilakukan oleh kepala sekolah SDN 200212/2 kota Padangsidimpuan provinsi Sumatera Utara sangat baik berada pada persentase 93% berdasarkan respon dari 20 guru. Sedangkan guru yang berada pada posisi netral melihat kepemimpinan kepala sekolah hanya 5% dan 2% lagi guru berpendapat bahwa kepala sekolah jarang memberikan penghargaan terhadap prestasi kerja serta tidak pernah adil memberikan sanksi kepada bawahan yang lalai melaksanakan tugas. Kata kunci: Kepala sekolah, mutu pendidikan, pandemi COVID-19